2017
DOI: 10.1007/s10461-017-1845-z
|View full text |Cite
|
Sign up to set email alerts
|

Interest in Long-Acting Injectable PrEP in a Cohort of Men Who have Sex with Men in China

Abstract: Long-acting injectable (LAI) formulations of antiretrovirals (ARVs) as pre-exposure prophylaxis (PrEP) could be an attractive alternative for men who have sex with men (MSM) who are interested in ARV-based biomedical prevention but will not use a daily pill. This study investigated interest in LAI-PrEP in a cohort of MSM in China and characterized how MSM willing to use only injectable PrEP differed from MSM who would use PrEP regardless of modality or not at all. Demographic, behavioral, and risk perception m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 26 publications
7
55
0
Order By: Relevance
“…Our data suggest that many Chinese MSM prefer injectable PrEP compared to oral PrEP. This finding is consistent with data from China [13] and the US [33]. The preference for injectable PrEP may be due to convenience, decreased frequency of medication taking, and less stigma [33,34].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our data suggest that many Chinese MSM prefer injectable PrEP compared to oral PrEP. This finding is consistent with data from China [13] and the US [33]. The preference for injectable PrEP may be due to convenience, decreased frequency of medication taking, and less stigma [33,34].…”
Section: Discussionsupporting
confidence: 89%
“…We found that interest in using PrEP was associated with using more than one HIV test in a year. MSM who used more than one HIV test in a year may either have riskier behaviors or higher self-perceived risk of acquiring HIV [13,21,30]. This finding also suggests that PrEP services could be integrated with HIV testing services.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Along with these PrEP promotion programs, awareness of PrEP (11-58% [5,[8][9][10][11][12]) and willingness to PrEP uptake (64-92%) [13,14] have increasing among MSM globally. The 2017 Chinese National Internet Survey among 4581 MSM showed that 22.4% of them had heard of PrEP and the majority (76%) would like to try PrEP [12].…”
Section: Introductionmentioning
confidence: 99%